2012
DOI: 10.1155/2012/908963
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Fine Needle Biopsy in Pancreatic Tumors: A Study of 42 Cases

Abstract: The technological progress within the range of methods of pancreas imaging and their more common accessibility selects a group of patients requiring a microscopic diagnosis. Percutaneous fine needle aspiration biopsy under the control of ultrasonography (PCFNA/USG) is the method commonly used in determining the character of a focal pancreatic lesion. Aim of the Work. An assessment of the accessibility of PCFNA biopsy in the assessment of solid and cystic changes in a pancreas and the correlation of the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…9,1113 Diagnostic performance is good, with a reported sensitivity of 92.5% and specificity of 68–100% for neoplasia. 11,13 Few studies have addressed pancreatic FNA in cats. 5,6,14 Although no complications have been reported in the 17 cats evaluated in these studies, speculation about potential risks following pancreatic sampling may contribute to the reluctance to perform pancreatic FNA.…”
Section: Introductionmentioning
confidence: 99%
“…9,1113 Diagnostic performance is good, with a reported sensitivity of 92.5% and specificity of 68–100% for neoplasia. 11,13 Few studies have addressed pancreatic FNA in cats. 5,6,14 Although no complications have been reported in the 17 cats evaluated in these studies, speculation about potential risks following pancreatic sampling may contribute to the reluctance to perform pancreatic FNA.…”
Section: Introductionmentioning
confidence: 99%
“…Desirable qualities for image‐guided biopsy are that it should be sensitive and accurate to characterize a lesion and be performed with low complication rates and consideration of patient comfort. Percutaneous biopsy of the pancreatic lesions is usually performed under the guidance of CT or US . However, the low contrast of soft tissues, exposure to ionizing radiation, and short‐lived enhancement of vessels after intravenous injection of an iodine‐based contrast agent limit the use CT‐guided biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative modality for biopsy of pancreatic lesions is imaging‐guided percutaneous core needle biopsy, which can provide a histologic specimen and does not require an endoscopic procedure or sedation. Computed tomography (CT) and ultrasound (US) are most often used for guiding percutaneous pancreas biopsy . Magnetic resonance imaging (MRI) offers many inherent advantages over CT and US in terms of superior soft‐tissue contrast resolution, blood flow‐empty action, a nonionizing nature, and direct multiplanar capabilities.…”
mentioning
confidence: 99%
“…In the past, studies of unequivocal cases of pancreatic biopsy were reported in which the term "atypical cells in inflammatory background" was used. That problem occurs in both endoscopic ultrasonography fine needle aspiration (EUS/FNA) and percutaneous fine needle aspiration (PCFNA) biopsies and usually results from necrosis, cystic degeneration, or sometimes massive inflammation in the vicinity of a drainage tube into the compressed common biliary duct [27][28][29]. From a time-perspective, the molecular solutions and immunocytochemistry barely support correct diagnosis and proper patient management.…”
Section: Pancreatic Cytologymentioning
confidence: 99%